A Trial of a Solar-Powered, Cooperative Sensor/Actuator, Opto-Acoustical, Virtual Road-Fence to Mitigate Roadkill in Tasmania, Australia - Bruce Englefield; Steven G. Candy; Melissa Starling; Paul D. McGreevy (Animals, 2019)
When wildlife and motor vehicles collide, the result for the animals is often death (roadkill). A commercial roadkill mitigation device that forms a so-called virtual fence (VF), is said to reduce roadkill by up to 90%. A field trial to test its effectiveness was undertaken along a 4.5-km segment of a Tasmanian highway subdivided into 6 equal sections. A total of 126 days of monitoring of roadkill by species was conducted, with alternate sections being switched on or off, according to a variation of Crossover and Multiple Before-After-Control-Impact experimental designs that divided monitoring into five periods. From the six sections over the five periods, the 30 aggregated values of daily counts of roadkill for each species were modelled. Bennett’s wallabies (BW) (Notamacropus rufogriseus), Tasmanian pademelons (TP) (Thylogale billardierii) and common brush-tail possums (BP) (Trichosurus vulpecula) accounted for most of the total roadkill of 174 animals. Although initially there appeared to be an effect, linear model fits to standardised roadkill rates were not statistically significant for each of BW, TP, and BP using each of the Crossover, Multiple Before-After-Control-Impact, and simple On versus Off comparisons. Adjustment for spatial and temporal trends using a Generalised Additive Model with Poisson error also failed to detect a significant VF effect. A simulation study used to estimate the power to detect a statistically significant reduction in roadkill rate gave, for median estimates of reduction of 21%, 48%, and 57%, estimates of power of 0.24, 0.78, and 0.91, respectively. Therefore, this study failed to confirm previously reported estimates of reduction in roadkill rates claimed for this VF of 50%−90%, despite having adequate power to do so. However, point estimates obtained for these three species of reductions ranging from 13% to 32% leave open the question of there being a real but modest effect that was below statistical detection limits.